Tratamento biológico de efluentes de lava-jato - Costa, Maria José Comandante (2006)
The research was realized in four phases. In the 1st phase, interviews were accomplished with proprietors of car-washes with the objective of knowing your environmental and social impacts. In the 2nd phase synthetic effluents of car-washes were treated during 147 days in batch anaerobic reactors with five different oil and detergent concentrations. In the 3rd phase six reactors were monitored in batch form, during 20 days, with substrate containing high oil concentrations (0,5 to 2,5 g.l-1) and surfactants concentrations (5,0g.L-1). These treatments were realized with purpose to verified the relation between oil concentration and inhibition of the biologic activity. In the 4th phase six batch anaerobic reactors, with different proportions of the surfactant, were monitored during 35 days. The concentrations of organic matter influent and effluent were analyzed in all the treatments and in the sludge were determined solid concentration. Daily the biogas produced was measures and characterized. In the 2nd phase the average removal of soluble COD was about 82%, for a monitoring period of 18 days. For raw COD during 100 days of operation the average removal was approximately 76% and the production of methane was directly proportional the substrate concentrations. It was verified that the anaerobic biological activity occurs in surfactant concentration below 0,5 g.L-1, and starting from that concentration it begins to happen inhibition of the process